STUDY OF CHARACTERISTICS OF GASIFICATION PROCESS OF VARIOUS BIOMASS IN A DOWNDRAFT GASIFIER - Agus Aktawan; Agus Prasetya; Wahyu Wilopo (Master in Systems Engineering, 2015)
Biomass gasification is an endothermic reaction process for converting biomass into syngas, occurs at high temperatures with limited oxygen. Knowing the temperature profile of biomass gasification wood charcoal, coconut shell charcoal and coconut shell, rice husk and woodchip and seek optimal results from gasification of biomass are the purpose of the research.The equipment in this research consisted of; gasifier as the main tool with 4 temperature sensors, two cyclones for tar and dust separator, cooler to refrigerate and filter containing biomass as a catcher of dust and tar from the syngas. Research start by ignite the biomass in the gasifier, the air flows by blower and the syngas came out after the filter. Research variabel are variation of biomass types mentioned above and variation of shell and coconut shell charcoal mixing. Observations were made up until the biomass in the gasifier did not produce syngas, characterized by gas results could not burn.The results of the temperature profile of gasification of various types of biomass shows that the syngas appeared in the early minutes (2 minutes until the 5th) on the gasification, such as gasification coconut shell, woodchip, rice husk. Syngas of coconut shell charcoal is 2,825% w/w of biomass and can burn for 19 minutes and resulted in 1,92% ash and 29,57% charcoal. Syngas of mixture 25% shell and 75% coconut shell charcoal is 5,013% w/w of biomass and can burn for 30 minutes and resulted in 1,61% ash and 5,1% charcoal.